Human dermal fibroblasts present tetanus toxoid antigen to antigen-specific T cell clones. - Umetsu, D T (1985)
Cultured human dermal fibroblasts treated with immune interferon express HLA-DR antigens. We report here that DR-positive fibroblasts present tetanus toxoid (TT) to autologous TT-specific monoclonal helper T cells vigorously depleted of monocytes by passage over Sephadex G10 columns followed by treatment with the monoclonal antibodies (mAb) OKM1 and Leu M1 plus complement. The extent of T cell proliferation in response to TT presented by DR-positive fibroblasts was similar to that elicited using monocytes as antigen-presenting cells. The proliferative response was TT dependent, antigen specific, depended upon DR expression by fibroblasts, appeared MHC restricted, and was completely blocked by mouse mAb to HLA-DR but not by mAb to HLA-A,B, or DQ. DR-positive fibroblasts pulsed with TT were similarly effective in antigen presentation. In summary, immune interferon-stimulated human dermal fibroblasts can substitute for classical antigen-presenting cells in antigen-specific proliferative responses. Since fibroblasts are a ubiquitous cell type in the body, they may play a significant role in the immunobiology of the host.